Telomere length in newborns is related to maternal stress during pregnancy - Send, Tabea; Sütterlin, Marc; Laucht, Manfred; Deuschle, Michael; Rietschel, Marcella; Witt, Stephanie (Neuropsychopharmacology, 2017)
Telomere length (TL) is a marker of biological aging, and numerous studies have shown associations between TL and somatic or psychiatric disorders. Research also indicates an association between maternal stress during pregnancy and TL in the offspring. The present study investigated possible associations between TL and: (1) maternal perceived stress during pregnancy; (2) a maternal lifetime history of psychiatric disorder (lifetime PD); and (3) paternal age. TL was analyzed in 319 newborns and 318 mothers from a predominantly Caucasian sample (n=273 Caucasian newborns and n=274 Caucasian mothers). Two key findings were observed. First, maternal perceived stress during pregnancy was associated with shorter telomeres in newborns but not with maternal TL. Second, maternal lifetime PD was associated with shorter maternal telomeres, but not with TL in newborns. Paternal age was not associated with TL in newborns. The finding that maternal stress during pregnancy is associated with shorter telomeres in newborns supports the results of smaller previous studies. The fact that a relation between maternal prenatal stress and TL was observed in the offspring but not in mothers may be attributable to a high vulnerability to stress during intrauterine development of a maturing organism. To our knowledge, this is the largest study to date to show that maternal stress during pregnancy but not maternal lifetime PD is associated with shorter telomeres in the offspring.